SUSTAINABLE ISLAMIC EDUCATION: INTEGRATING GREEN CAMPUS CONCEPTS IN ISLAMIC UNIVERSITIES - Sugito Sugito (Penelitian dan Pengembangan Ilmu, 2025)
Sustainable Islamic education is important in facing global environmental challenges, such as climate change and pollution. Islamic universities have a strategic role in internalizing sustainability values ​​into the curriculum and daily operations. This research aims to explore the application of the Green Campus concept in Islamic universities, with a focus on policies, practices and their impact on environmental awareness among students. The approach used is a systematic literature review by collecting data from journal articles, institutional policies, and interviews with stakeholders. Analysis was carried out through content analysis to identify the main themes related to the implementation of the Green Campus. Research findings show that the implementation of Green Campuses in Islamic universities varies, influenced by institutional policies, environmental awareness, and involvement of the academic community. Effective sustainability initiatives can increase ecological awareness and reduce a campus' carbon footprint. This research makes a significant contribution to the development of sustainable Islamic education by offering a Green Campus implementation model based on Islamic values. It is hoped that these findings can encourage more sustainable policies and practices in Islamic higher education.